Mechanochemical synthesis of indolyl chalcones with antiproliferative activity. Issue 2 (3rd April 2022) - Kudličková, Zuzana; Stahorský, Martin; Michalková, Radka; Vilková, Mária; Baláž, Matej
ABSTRACT: An efficient eco-friendly one-step mechanochemical synthesis of indole hybrid chalcones via the Claisen–Schmidt condensation of 1-methylindole-3-carboxaldehyde with various substituted acetophenones is described using liquid assisted grinding in a high-energy ball mill. The notable advantages of the present method are small organic solvent required (100 μL ethanol) and mainly shorter reaction time (15–60 min) as compared to the conventional method. Antiproliferative activity of synthesized chalcones was studied on several human cancer cell lines (MCF-7, HeLa, A549, MDA-MB-231, HCT116) and non-cancer lines (Cos-7 or BJ-5ta). 3, 4, 5-Trimethoxyphenyl 3g, 2, 5-dimethoxyphenyl 3h, and 2, 4, 5-trimethylphenyl 3j chalcones showed considerable cytotoxicity, particularly, chalcones 3h and 3j were identified as the most potent and selective anticancer agents with IC50 values 7.9 and 6.6 μM, respectively, against the colon cancer HCT116 cell line. GRAPHICAL ABSTRACT: UF0001